2011
DOI: 10.1371/journal.pone.0023748
|View full text |Cite
|
Sign up to set email alerts
|

Can Simply Answering Research Questions Change Behaviour? Systematic Review and Meta Analyses of Brief Alcohol Intervention Trials

Abstract: BackgroundParticipant reports of their own behaviour are critical for the provision and evaluation of behavioural interventions. Recent developments in brief alcohol intervention trials provide an opportunity to evaluate longstanding concerns that answering questions on behaviour as part of research assessments may inadvertently influence it and produce bias. The study objective was to evaluate the size and nature of effects observed in randomized manipulations of the effects of answering questions on drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
215
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(230 citation statements)
references
References 51 publications
(107 reference statements)
13
215
2
Order By: Relevance
“…For example, baseline questions about alcohol consumption may increase awareness and subsequently reduce instances of binge drinking because participants may realize that their alcohol intake is excessive through their interaction with a questionnaire. Therefore, in trials where an intervention designed to reduce drinking behavior is tested against a control condition, baseline assessment may mask or reduce observed intervention effects (McCambridge & Kypri, 2011). Moreover, in some trials, individuals allocated to an intervention group could receive different forms of measurement in order to tailor intervention components to participants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, baseline questions about alcohol consumption may increase awareness and subsequently reduce instances of binge drinking because participants may realize that their alcohol intake is excessive through their interaction with a questionnaire. Therefore, in trials where an intervention designed to reduce drinking behavior is tested against a control condition, baseline assessment may mask or reduce observed intervention effects (McCambridge & Kypri, 2011). Moreover, in some trials, individuals allocated to an intervention group could receive different forms of measurement in order to tailor intervention components to participants.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Most trials use self-reported alcohol consumption as their primary outcome measure rather than alcohol-related morbidity or mortality problems, and such self-reported outcomes may be subject to social desirability bias or other research participation effects. 14,15 Furthermore, the active ingredients of SBI have yet to be determined. 16,17 Notwithstanding these discussions, it is clear that alcohol increases the risk of and/ or exacerbates many conditions that present in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Brief interventions can vary in their degree of complexity and duration, ranging from the provision of simple advice through to several sessions of motivational interviewing, and delivered by either the person who administered the screening test, a specialist nurse or via SMS, web or email. 17,18 There is some evidence to suggest that simply asking questions about consumption can change behaviour, 19 and that accepting an appointment with an alcohol health worker is as effective as actually attending one. 20 Recent reviews of the evidence suggest that male AUD patients benefit more from brief interventions than females in both primary care and emergency department settings.…”
Section: Effective Interventionmentioning
confidence: 99%